Differential responses to avian pathogenic E. coli and the regulatory role of splenic miRNAs in APEC infection in Silkie chickens - Li, Wenqing; Li, Wanli; Wu, Pinhui; Jin, Wei; Yuan, Lin; Wang, Bingxun; Li, Shengli; Kang, Xiangtao (Frontiers in Cellular and Infection Microbiology, 2024)
Avian pathogenic Escherichia coli (APEC) is a bacterial disease that harms the poultry industry worldwide, but its effect on Chinese Silkie has not been reported. Studies on whether there are differences in Silkie individual resistance to APEC and the regulatory role of spleen miRNAs lay the foundation for strategies against APEC. Therefore, 270 Silkie chickens were infected with the median lethal dose of an E. coli O1, O2, and O78 mixture. These chickens were divided into a susceptible group (Group S) and a recovery group (Group R) according to whether they survived 15 days postinfection (dpi). Moreover, 90 uninfected APEC Silkie served as controls (Group C). The splenic miRNA expression profile was examined to evaluate the role of miRNAs in the APEC infection response. Of the 270 Silkies infected with APEC, 144 were alive at 15 dpi. Cluster analysis and principal component analysis (PCA) of splenic miRNAs revealed that the four Group R replicates were clustered with the three Group C replicates and were far from the three Group S replicates. Differentially expressed (DE) miRNAs, especially gga-miR-146b-5p, play essential roles in immune and inflammatory responses to APEC. Functional enrichment analyses of DEmiRNAs suggested that suppression of immune system processes (biological processes) might contribute to susceptibility to APEC and that FoxO signaling pathways might be closely associated with the APEC infection response and postinfection repair. This study paves the way for screening anti-APEC Silkies and provides novel insights into the regulatory role of miRNAs in APEC infection.